2-2(b-3)=-4(b+1)

Simple and best practice solution for 2-2(b-3)=-4(b+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-2(b-3)=-4(b+1) equation:


Simplifying
2 + -2(b + -3) = -4(b + 1)

Reorder the terms:
2 + -2(-3 + b) = -4(b + 1)
2 + (-3 * -2 + b * -2) = -4(b + 1)
2 + (6 + -2b) = -4(b + 1)

Combine like terms: 2 + 6 = 8
8 + -2b = -4(b + 1)

Reorder the terms:
8 + -2b = -4(1 + b)
8 + -2b = (1 * -4 + b * -4)
8 + -2b = (-4 + -4b)

Solving
8 + -2b = -4 + -4b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '4b' to each side of the equation.
8 + -2b + 4b = -4 + -4b + 4b

Combine like terms: -2b + 4b = 2b
8 + 2b = -4 + -4b + 4b

Combine like terms: -4b + 4b = 0
8 + 2b = -4 + 0
8 + 2b = -4

Add '-8' to each side of the equation.
8 + -8 + 2b = -4 + -8

Combine like terms: 8 + -8 = 0
0 + 2b = -4 + -8
2b = -4 + -8

Combine like terms: -4 + -8 = -12
2b = -12

Divide each side by '2'.
b = -6

Simplifying
b = -6

See similar equations:

| 20+12i= | | 6(x+7)-8=6x-8 | | 2x-4y+3z=8 | | (6x+1)(x+3)=0 | | 77=-(v-7)-5(7+4v) | | 13a+7=4(a+4) | | 27+9x=4x-5x | | 7.00+1.50p=29.50 | | .33x+4=17 | | 2q^2-5q-25=0 | | X^3=117649 | | 5b-7b=-4(b+2)+4(b-6) | | 7-(m+4)=2(2m-5) | | An=8n-10 | | 6x-7=x+38 | | 56-24+56-96= | | 19x^2+16=0 | | 0.2b+4=0.5b+16 | | 4x-1=9x-15x | | 2x+2.3=7.1 | | 2x-9x+5x-7x= | | x^3+6x^2+13x=0 | | 3(4-2x)=5(2-x) | | 6x+16=4(x+6) | | (2x+9)+(2x+8)+(2x)=(2x)+(2x)+(3x+5) | | y=Ax^3+Bx^2+Cx | | 3(r-4)=-9 | | 64m^2+144m+81=0 | | 6(x+9)=-26-4x | | 8+10x= | | 21-a+4a=6 | | 2+6(7-x)=20 |

Equations solver categories